2017
DOI: 10.1002/aoc.3781
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of reduced graphene oxide/Fe3O4/Ag ternary nanohybrid and its application as magnetically recoverable catalyst in the reduction of 4‐nitrophenol

Abstract: Materials having both magnetic and catalytic properties have shown great potential for practical applications. Here, a reduced graphene oxide/iron oxide/silver nanohybrid (rGO/Fe3O4/Ag NH) ternary material was prepared by green synthesis of Ag on pre‐synthesized rGO/Fe3O4. The as‐prepared rGO/Fe3O4/Ag NH was characterized using Fourier transform infrared spectroscopy, X‐ray diffractometry, Raman spectroscopy, vibrating sample magnetometry, transmission electron microscopy and energy‐dispersive X‐ray spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The XRD pattern related to magnetic iron oxide nanoparticles shows seven peaks at 21.97, 30.18, 35.64, 42.83, 54.51, 57.15, and 63.09°, confirming the crystalline surfaces (111), (220), (311), (400), (422), (511), and (440) of these nanoparticles. This observation is in good agreement with patterns reported in the literature [ 43 ]. The XRD pattern of the synthesized nanocomposite clearly displays all peaks corresponding to the structures of silver nanoparticles and magnetic nanoparticles.…”
Section: Resultssupporting
confidence: 93%
“…The XRD pattern related to magnetic iron oxide nanoparticles shows seven peaks at 21.97, 30.18, 35.64, 42.83, 54.51, 57.15, and 63.09°, confirming the crystalline surfaces (111), (220), (311), (400), (422), (511), and (440) of these nanoparticles. This observation is in good agreement with patterns reported in the literature [ 43 ]. The XRD pattern of the synthesized nanocomposite clearly displays all peaks corresponding to the structures of silver nanoparticles and magnetic nanoparticles.…”
Section: Resultssupporting
confidence: 93%
“…Herein, multi-walled carbon nanotubes (MWCNTs)/Fe 3 O 4 /Ag composites were also fabricated in a biomolecular-assisted method as the control. Although with no reports of MWCNTs/Fe 3 O 4 /Ag composites used as a good material for pollutant treatment, the carbon-based/Fe 3 O 4 /Ag composites have been widely used in the field of photocatalysis. Compared with MWCNTs/Fe 3 O 4 /Ag, PC/Fe 3 O 4 /Ag shows a significant advance in performance. About the same degradation rate can be reached under the condition where only half of the catalyst and hydrogen peroxide were used.…”
Section: Introductionmentioning
confidence: 99%
“…These two factors in hybrid materials consisting of magnetic and graphitic nanostructures present an attractive tool for making a heterogeneous graphene-like material. 23 As examples using the adsorption capacity and the separation convenience of the magnetic materials, Wu has reported a new application of Fe 3 O 4 @CuO&GO for the removal of arsenic( iii / v ) from water. 24 Similar to this study, Doan and co-workers have shown that a ternary Fe 3 O 4 /CuO@C composite can be used as a photocatalyst for the degradation of the ciprofloxacin antibiotic.…”
Section: Introductionmentioning
confidence: 99%